Aetiological Diagnosis of Pleural Eusion: A cross sectional study (Bangladesh Medical Journal, 2019)
Pleural effusion is a common clinical problem with different possible causes. It can be due to local, systemic, infectious or non-infectious causes. Aetiological diagnosis is important for proper treatment. To evaluate the aetiological diagnosis of pleural effusion of hospitalized adult patients this cross-sectional, descriptive study conducted from April to September 2012 at Bangabandhu Sheikh Mujib Medical University (BSMMU). A total of 100 cases were selected by purposive sampling. Data were collected using a structured questionnaire. Complete history was taken either from patient or accompanying attendants. Clinical examination was done and relevant investigations report were collected. Data were analyzed using statistical package for the social sciences (SPSS). The mean age of the patient was 41.2 SD± 7.4 years with a male to female ratio of 3:1. Over half (52%) of the patients were poor, 34% were middle class and 14% were rich. Over two-third (67%) of the patients were smoker and the remaining 33% were non smoker. Out of 100 patients with pleural effusion, 52 had tuberculosis and 16 patients had malignancy. Among the malignant cases 14 were found to have bronchial carcinoma  and 2, had lymphoma. The remaining 32 patient had other causes of pleural effusion which included nephrotic syndrome 14, congestive cardiac failure 5, cirrhosis of liver 4, rheumatoid arthritis 3, amoebic liver abscess 2, and undiagnosed 4. Tuberculosis is the predominant cause of pleural effusion in our country and the second leading cause is malignancy.Bangladesh Med J. 2018 May; 47 (2): 29-34